Using Mixed Methods to Study Emotional Intelligence and Teaching Competencies in Higher Education - Akhmetova, J. B.; Kim, A. M.; Sadykova, A. T.; Harnisch, D. (ҚазҰУ Хабаршысы. Психология және әлеуметтану сериясы, 2016)
Education is one of the largest factors in the development of an independent country, especially for such a young country (22 years of independence) as Kazakhstan. The Bologna process was accepted in Kazakhstan only three years ago. This has created a new paradigm in education: competence-based education. Joining the western system of education has caused the changings in teaching characteristics and style. The modern system encourages teachers to be more mobile, which requires qualities such as emotional intelligence and communication competence. The purpose of this article is to examine the extent to which the competence-based approach has been implemented in the education system of Kazakhstan in terms of mixed methods research approach. The paper outlines the design of the study on emotional intelligence and teaching competence.